The internal and external responsiveness of Functional Assessment of Cancer Therapy-Prostate (FACT-P) and Short Form-12 Health Survey version 2 (SF-12 v2) in patients with prostate cancer - Choi, Edmond P. H.; Wong, Carlos K. H.; Wan, Eric Y. F.; Tsu, James H. L.; Chin, W. Y.; Kung, Kenny; Yiu, M. K. (Quality of life research, 2016)
Purpose To examine the responsiveness of Functional Assessment of Cancer Therapy-Prostate (FACT-P) and Short Form-12 Health Survey version 2 (SF-12 v2) in prostate cancer patients because there is a lack of evidence to support their responsiveness in this patient population. Methods One hundred sixty-eight subjects with prostate cancer were surveyed at baseline and at 6 months using the SF-12 v2 and FACT-P version 4. Internal responsiveness was assessed using paired t test and generalized estimating equation. External responsiveness was evaluated using receiver operating characteristic curve analysis. Results The internal responsiveness of the FACT-P and SF-12 v2 to detect positive change was satisfactory. The FACT-P and SF-12 v2 could not detect negative change. The FACT-P and the SF-12 v2 performed the best in distinguishing between improved general health and worsened general health. The FACT-P performed better in distinguishing between unchanged general health and worsened general health. The SF-12 v2 performed better in distinguishing between unchanged general health and improved general health. Conclusions Positive change detected by these measures should be interpreted with caution as they might be too responsive to detect "noise," which is not clinically significant. The ability of the FACT-P and the SF-12 v2 to detect negative change was disappointing. The internal and external responsiveness of the social well-being of the FACT-P cannot be supported, suggesting that it is not suitable to longitudinally monitor the social component of HRQOL in prostate cancer patients. The study suggested that generic and disease-specific measures should be used together to complement each other.